Does Owner’s Competence and Skill Drive Small Business Performance - Marampa, Adriana Madya; Afandi, Mugiarti; Adawiyah, Wiwiek Rabiatul (Future Science, 2021)
Competence is needed in every scope of the company, including micro and small, and medium enterprises. Competence to manage a business is needed to improve performance. In determining whether or not a business is booming, one of the supporting factors is competency. This study uses quantitative methods by distributing questionnaires purposively to MSME employees in various regions in Indonesia. 300 questionnaires were distributed and 150 were returned. This research was conducted for about 6 months. The data processing method used is using the SEM -PLS method. This questionnaire's dissemination was distributed in various places in Indonesia, namely in Tana Toraja, Purwokerto, and Ajibarang. The questionnaires distributed were around 300. The return was 131. The research method was quantitative using a simple regression method. The results showed that the relationship between Knowledge Competence and MSME Performance was significant, with a T-statistic of 3.479 (> 1.96). The original sample estimate value is positive, which is 0.253, which shows that the relationship between Knowledge Competence and MSME Performance is positive. Thus, the H1 hypothesis is accepted, Showing that the relationship between Attitude Competence and MSME Performance is significant, with a T-statistic of 4.316 (> 1.96). The original sample estimate value is positive, which is 0.323, which indicates that the direction of the relationship between Attitude Competency and MSME Performance is positive. Thus, the H2 hypothesis is accepted.